1995
DOI: 10.1093/jn/125.7.1875
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Trichuris trichiura Infections Improves Growth, Spelling Scores and School Attendance in some Children

Abstract: The effects of treating Trichuris trichiura infections were investigated in 407 Jamaican children age 6 to 12 y. The children were randomly assigned to receive treatment (albendazole) or a placebo. The outcome variables included growth, tests of reading, spelling and arithmetic, and school attendance. After 6 mo of treatment, there was no significant main effect on any of the outcomes. However, there were significant treatment-by-infection intensity interactions with spelling (P < 0.05) and body mass index (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 19 publications
3
75
1
Order By: Relevance
“…The interaction effects with treatment indicated that it was children who were more heavily infected with S. japonicum (Ͼ median of 30 epg), or who had lower hemoglobin levels (Ͻ median of 11.7g/dL) or who were more chronically undernourished (height-for-age Ͻ median of Ϫ1.7) who benefited the most from treatment. This is analogous to the findings of Simeon and others, 5,6 in which after treatment for T. trichiura infection, children who were initially the most heavily infected or the most undernourished (weightfor-age Ͻ Ϫ 2 SD) showed the greatest improvement in Spelling and in Fluency test scores, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The interaction effects with treatment indicated that it was children who were more heavily infected with S. japonicum (Ͼ median of 30 epg), or who had lower hemoglobin levels (Ͻ median of 11.7g/dL) or who were more chronically undernourished (height-for-age Ͻ median of Ϫ1.7) who benefited the most from treatment. This is analogous to the findings of Simeon and others, 5,6 in which after treatment for T. trichiura infection, children who were initially the most heavily infected or the most undernourished (weightfor-age Ͻ Ϫ 2 SD) showed the greatest improvement in Spelling and in Fluency test scores, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…[1][2][3][4][5][6][7] The specific effects on mental function are not clear and may depend not only on the duration and intensity of infection but also on the species of parasitic infection and whether or not the parasites are present as single or multiple species infections.…”
mentioning
confidence: 99%
“…Younger children are predisposed to heavy infections with intestinal parasites since their immune systems are not yet fully developed (3), and they also habitually play in faecally contaminated soil. In addition to considerable mortality and morbidity, infection with intestinal helminths has been found to profoundly affect a child's mental development, growth and physical fitness while also predisposing children to other infectious agents (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, A. lumbricoides can cause blockage of the intestine and T. trichiura has been associated with dysentery (Cooper et al 1992). Both helminths have also been associated with stunted growth (Cooper & Bundy 1988, Stephenson et al 1989, 1993, Adams et al 1994, Simeon et al 1995, Hadju et al 1996, Saldiva et al 1999) and impaired cognitive functions in children (Nokes et al 1992a, b, Oberhelman et al 1998. Another common soil transmitted helminth that causes severe morbidity and is often found with A. lumbricoides and T. trichiura infections is hookworm (WHO 1987).…”
mentioning
confidence: 99%